2015
DOI: 10.1038/cddis.2015.102
|View full text |Cite
|
Sign up to set email alerts
|

Peptides derived from the dependence receptor ALK are proapoptotic for ALK-positive tumors

Abstract: ALK is a receptor tyrosine kinase with an oncogenic role in various types of human malignancies. Despite constitutive activation of the kinase through gene alterations, such as chromosomal translocation, gene amplification or mutation, treatments with kinase inhibitors invariably lead to the development of resistance. Aiming to develop new tools for ALK targeting, we took advantage of our previous demonstration identifying ALK as a dependence receptor, implying that in the absence of ligand the kinase-inactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Additionally, synthetic peptides corresponding to the proapoptotic domain of ALK caused p53-mediated cytotoxicity in ALCL and neuroblastoma cells (31). In the same study, ALK peptides interacted with proteins that have been previously reported to interact with the p53 gene and protein.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, synthetic peptides corresponding to the proapoptotic domain of ALK caused p53-mediated cytotoxicity in ALCL and neuroblastoma cells (31). In the same study, ALK peptides interacted with proteins that have been previously reported to interact with the p53 gene and protein.…”
Section: Discussionmentioning
confidence: 99%
“…One crucial characteristic of ALK is that it is a so-called dependence receptor [ 39 , 40 , 41 ] ( Figure 2 ). Without ligand binding to activate its kinase activity, ALK can be cleaved by caspase-3 during apoptosis [ 39 , 40 , 41 ]. In the juxtamembrane region of ALK, there is a caspase-3 cleavage site (amino acids 1160–1163: DELD) ( Figure 2 ).…”
Section: Alk Is a Dependence Receptormentioning
confidence: 99%
“…Elevated caspase-3 activity can cleave this ALK at this cleavage site, which releases an intracellular ALK fragment (about 60 kDa) into the cytoplasm. This caspase-dependent cleavage of ALK enhances apoptosis through the exposure of a pro-apoptotic segment (addiction/dependence domain, ADD) within the ALK juxtamembrane region [ 39 , 40 , 41 ]. ALK mutant D1160N abolishes the caspase-3 cleavage at this cleavage position, which also abrogates the ALK-mediated enhancement of apoptosis [ 39 , 40 , 41 ].…”
Section: Alk Is a Dependence Receptormentioning
confidence: 99%
See 2 more Smart Citations